Liquidity, Solvability on Profibitality: A Study on Consumption Companies Listed at Indonesian Stock Exchange - Gracia Naibaho; Francis Hutabarat (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2020)
This study aims to examine the effect of Liquidity and Solvency on Profitability. The sample of this study was 10 consumption companies consisting of four cigarette companies (WIIM, GGRM, HMSP, RMBA) and six cosmetics companies (ADES, KINO, MBTO, MRAT, TCID, UNVR). Thus the research sample was found to be 40. The research variable used one dependent variable, namely profitability using the return on assets and two independent variables, namely liquidity using inventory to net working capital and current ratio and solvency using debt to equity ratio. This research uses descriptive data analysis, coefficient of determination analysis, regression analysis and data analysis using the SPSS application. The results showed that the Current Ratio did not significantly influence profitability. Inventory to Net Working Capital has a significant effect on profitability. Debt to Equity ratio has a significant effect on profitability. And Current Ratio, Inventory to Net Working Capital simultaneously have a significant effect on the profitability (ROA) of Consumption Companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2018 period. significant value0.002 <0.05